IMPLEMENTASI METODE HOUSE OF RISK PADA EVALUASI KETERLAMBATAN PROYEK RENOVASI GEDUNG AULA PP3 BLITAR UM - Abu Rizal Firmansyah; Nina Aini Mahbubah (SIGMA TEKNIKA, 2022)
CV. DDD is a company engaged in construction services. In the construction of the Pp3 Blitar Hall renovation project, State University of Malang, there was a delay in project completion which had an impact on the quality of the project. In project work, there are several things that are required to be taken into consideration including finance, equipment, materials, labor, and time. So based on these considerations, the work in a project can be carried out properly. Project management needs to be done, so that the smooth running of the project can be carried out properly and optimally. The purpose of this study is to identify risk events and risk agents the factors that cause project delays. House of Risk is the method used in this research. The results of this study are the identification of risk events against the analysis of project delays, there are twelve risk events and 15 potential causes of risk events. This research also produces scenarios of five priority mitigation strategies, namely purchasing materials planned for weekly or monthly needs, looking for closer suppliers, buying lots at lower prices and sufficient safety stock and applying the material requirements planning method to find out more details of the lead time of each material.